Identification and Strategy Tourism Attractions Memorial Surabaya - Lokajaya, I Nyoman (Archives of Business Research, 2020)
The objectives of this study are 1) to identify the area as an object of memorial tourism attraction which triggers a battle event on November 10, 1945, 2) Generate a strategy that supports the attraction of memorial Surabaya tourism. The research method used is qualitative research with a phenomenological approach. By using the interpretative phenomenological analysis method, it were 1) Obtained 20 objects of memorial tourist attraction which triggered the November 10, 1945 battle events from the Jalan Bubutan (GNI Building, Viaduct) to the Jalan Tunjungan (Siola, Yamato/Majapahit Hotel). 2) Strategies that support the attraction of Surabaya memorial tourism are a) Introduction and promotion of the cultural sites of heritage sites (building heritage sites) Surabaya through the Tourism Information Center, b) Instilling heroic historical values of Surabaya through memorial tours, c) Maintenance of existing cultural heritage, d) Hold a historical river tourism event with a route from the Petekan Bridge to the Jalan Pemuda Bridge (near Gubeng Pojok).